Doktrin Kristus / Kristologis - Linda lestari Kueain; Nani sunarsi; Dia Mirsa; Melin; Sarmauli (An Nafi': Multidisciplinary Science, 2024)
The purpose of this article is to explain the development of doctrinal thinking regarding Christ in Church history and provide a biblical foundation related to this doctrine. Some selective choices regarding the thoughts of certain theologians, both supportive and not, in the early centuries of the history of the Birth of Christ and the period after, will be taken to explain the doctrine of Christ. However, the target to be achieved is to strengthen the doctrine of Christ which is related to salvation and the mystery of faith. In the presentation of this article, the method used is through explanation from the perspective of historical theology of several Patristic theological thoughts and certain councils as well as biblical foundations taken selectively to support teaching about the incarnation. The thesis statement is that the doctrine of the incarnation is a fundamental teaching of the Christian faith and this is strengthened through Church tradition (historical theology) and a strong biblical foundation.